Analisis Hasil Belajar dan Persepsi Peserta terhadap Faktor-Faktor Pelatihan pada Diklat Teknis Kelapa Sawit - Marhaenis Budi Santoso (Bidang Penyelenggaraan, Kelembagaan dan Ketenagaan Pelatihan - Pusat Pelatihan Pertanian - Badan Penyuluhan dan Pengembangan Sumber Daya Manusia Pertanian - Kementerian Pertanian, 2018)
This study was aimed to determine improvements in learning outcomes based on knowledgeindicators before and after training, and to analyze training factors such as training materials,facilities and infrastructure, facilitators, and training methods.The data of learning result was collected by initial test and final test. The data of participants’response was collected by a linkert scale list. To express the increase in learning outcomes, thedata was calculated by the Normalized Gain formula. To compare the result of initial test andfinal test were done by using T test. To find out the participants’ responses, the data were analyzeddescriptively by counting the number of scores in the questionnaire submitted to responsdens.The results of the study showed that participants responded well to the programs, materials,facilities, facilitators, and methods used. The increase in learning outcomes of most participants(86.66%) were classified into moderate category (30% <Normalized Gain <70%). The averageinitial test score was 39.00, and the final test was 70.50. The result of test with T test shows that thevalue of Tscore was 13,331 higher than Ttabular (1.70) at 95% confidence level, and Ttabular (2,46)at 99% confidence level. This means that there was a significant. The increase in score indicatesthat the training that has been held was effective.